FAKTOR-FAKTOR YANG MEMPENGARUHI SERVICE PER CONCEPTION PADA SAPI KRUI DI KECAMATAN PESISIR SELATAN - Nur Fadilah Rizki Fauzi; Madi Hartono; Siswanto Siswanto; Sri Suharyati (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
Research on service per conception (S/C) of Krui Cattles in Pesisir Selatan Regency was carried out in December 2019 using two inseminators collection data, 75 farmers and 166 Krui Cattles that have been artificially inseminated. The purpose of this study was to determine: 1) the S/C value of Krui cattle in the Pesisir Selatan District, 2) the factors and its magnitude that influence the S/C of Krui cattle in Pesisir Selatan Regency. Data was analysed with multiple regression using SPSS (Statistical Package for Social Science) programs. The results showed that the S/C value of Krui Cattles in Pesisir Selatan Regency was 1.53±0.71. The factors that affected the S/C value of Krui Cattless in Pesisir Selatan Regency were derived from the variable of farmers and livestock. At the farmer level the factors that influence wee the type of forage that is negatively associated with a factor of 0.229, the shape of the cage wall which is negatively associated with 0.287, and the sanitation of the cage that is negatively associated with 0.355. Factors influencing S/C values at the livestock level were negative associated body condition scores (BCS) of 0.429, age of first mated was negative associations of 0.039, and estrus postpartum negative associations of 0.118. Keywords: Factors and factors value, Service per conception, Krui cattle